Social Reporting in the Italian Justice System: Milan Court Experience. (2nd July 2016) - Ricci, Paolo; Fusco, Floriana
Abstract : This research analyzes social reporting in Italian court offices, focusing in particular on the latest Milan Court social report, and underlining the problems encountered by operators when applying social reporting methodologies to complex organizations. The results are not very satisfactory—the deficiencies identified do not allow overcoming the three major issues that voluntary reporting entails. In summary, the research shows how difficult it is to adopt social reporting procedures within complex institutions and the need to elaborate new methodologies. Social reporting can have a fundamental role in generating public value; therefore the study is far from over, because of the importance of checking, in the future, the progress (or regress) of judicial offices along this path and to consider the need to create a specific model for these public entities.